Fair Value Determination for Minority Shareholder Appraisal Rights: Comparative Indonesia and Singapore - Adin Pramudito Nugroho (Yayasan Cerdas Pedia Indonesia, 2026)
Indonesian corporate law formally recognizes minority shareholder appraisal rights but lacks methodological parameters for fair value determination, rendering statutory protections completely ineffective against majority shareholder oppression. This study conducts normative legal research utilizing statutory, conceptual, and comparative approaches to effectively contrast Indonesian regulations with Singaporean jurisprudence and global corporate valuation standards. Results reveal that Singapore proactively replaces statutory appraisal rights with comprehensive oppression remedies, empowering courts to strictly enforce commercial fairness via mandatory buyouts that absolutely prohibit minority discounts. In stark contrast, Indonesia's existing normative void systemically facilitates structural asymmetry and massive wealth appropriation. To fix this legal vacuum, Indonesia must rapidly reconstruct its corporate litigation framework by statutorily adopting established commercial fairness doctrines. Legislators must explicitly mandate binding judicial guidelines requiring independent financial valuers and formally abolish all minority discount applications. This vital systemic integration will successfully elevate domestic corporate governance toward superior global dispute resolution quality and justice.